Research on Price Influencing Factors of Third-Party Payment Platforms: An Empirical Study From China - Wang, Na; Liu, Wen; Shi, Jinping (Frontiers in Psychology, 2022)
In this paper, we use the two-sided market theory as a support and take the operating data of eight third-party payment platform companies as samples, basing on pricing models and multiple regression analysis to build a price feature model for third-party payment platform. The results show that under the two-sided market environment, the scale of consumer and the same-side network externality of the merchant have a negative significant effect on the pricing of third-party payment platform to the seller; the market share of platform and the bank fee cost of the platform have a positive significant effect on the pricing of third-party payment platform to the merchant; At the same time, the same-side network externality of the seller, the scale of merchant, and the selection of business model of the platform have no significant effect on the pricing of third-party payment platform to the merchant. These conclusions provide a scientific basis for a third-party payment platform enterprise to develop an appropriate pricing strategy and operating model.